AN ANALYSIS OF LANGUAGE FUNCTION USED BY THERAPIST AND GUEST IN RITUAL SPA RAMAYANA RESORT & SPA - Sari, Ni Putu Shintya Permata; Utami, Ni Made Verayanti; Maharani, Putu Devi (LPPM Universitas Dhyana Pura, 2020)
ABSTRACTThis study discusses language function and the expression of language function that aimsto determine the types of language function used by the therapist in Ritual Spa RamayanaResort & Spa, and to analyze the types of language function expression. The study utilizes astudy by Tillit and Bruder (1985) as the referenced theory to answer the research problems.The data source is taken from the conversation between the therapists and guests from escortingthe guest until giving the ginger tea after doing the treatment. The data was collected by usingthe observation method, using a voice recorder and note-taking techniques. The transcripts ofvoice recording were classified into the types of language functions and expression of languagefunction. The data analysis employs the qualitative method. There are 24 data points fromtwelve conversations. The data was classified into six types of language function and threetypes of expression. The types of language functions found in the conversations includeopening, pre-closing, closing, introduction and address system, invitation, thanking people andreplying to thanks, gaining attention and interrupting, as well as agreeing and disagreeing. Theexpressions include formal, informal, and neutral forms of expression. The data of languagefunction and expression was classified and presented in tables and described narratively indeeper analysis related to the theory.Keywords: language function, expression, conversationABSTRAKPenelitian ini berkaitan dengan fungsi bahasa dan ekspresi fungsi bahasa yangbertujuan (1) Untuk mengetahui jenis fungsi bahasa yang digunakan oleh terapis di Ritual SpaRamayana Resort & Spa dan (2) Untuk menganalisis jenis-jenis ekspresi fungsi bahasa yangdigunakan oleh terapis di Ritual Spa Ramayana Resort & Spa. Teori yang digunakan untukmenjawab masalah penelitian ini dituju oleh Tillit dan Bruder (1985) dengan sebuah bukuberjudul Speaking Naturally. Sumber data penelitian ini diambil dari percakapan terapisdengan tamu sambil mengantar tamu sampai memberikan teh jahe setelah melakukanperawatan. Data dikumpulkan dengan menggunakan metode observasi. Oleh karena itu, datadirekam oleh perekam suara dan mencatat percakapan. Transkrip rekaman suaradiklasifikasikan ke dalam jenis fungsi bahasa dan ekspresi fungsi bahasa. Metode kualitatifadalah digunakan dalam menganalisis data. Ada dua puluh empat data yang ditemukan dalamdua belas percakapan terapis dengan tamu di Spa. Dua puluh empat data diklasifikasikan kedalam enam jenis fungsi bahasa dan tiga jenis ekspresi. Jenis-jenis fungsi bahasa ditemukandalam percakapan terapis dan tamu membuka, pra-penutupan, penutupan, pengenalan dansistem alamat, undangan, berterima kasih kepada orang-orang dan membalas terima kasih,mendapatkan perhatian dan gangguan orang, setuju dan tidak setuju. Ekspresi yang ditemukan adalah ekspresi formal, informal, dan netral. Data fungsi dan ekspresi bahasa diklasifikasikandan disajikan dalam bentuk tabel dan dideskripsikan secara naratif dalam analisis yang lebihmendalam terkait dengan teori.Kata kunci: fungsi Bahasa, ekspresi, percakapan